2020
DOI: 10.24171/j.phrp.2020.11.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Virulence and Antimicrobial Resistance Markers of Enterovirulent <italic>Escherichia Coli</italic> from Fecal Isolates of Adult Patients with Enteric Infections in West Cameroon

Abstract: This study aimed to identify virulent and antimicrobial resistant genes in fecal E. coli in Mbouda, Cameroon. Methods: A total of 599 fecal samples were collected from patients with enteric infections who were ≥ 20 years old. E. coli was isolated on the MacConkey agar and virulent genes were detected by multiplex/ simplex PCR. Isolates in which ≥ 1 virulent gene was detected were subjected to antibiotic susceptibility testing. The resulting resistant isolates were subjected to PCR, followed by sequencing for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the study population, patients' age ranging from 5 to 50 years old showed a high frequency of isolation of diarrheic E. coli. Our result is similar to that obtained for patients of ages ranging between 20 to 50 years old (20 to 30 years old, 26.89%; 30 to 40 years old, 18.49%; 40 to 50 years old, 30.25%) by Marbou et al [36]. However, in this study, no isolates were obtained from children aged between 0 to 5 years old.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study population, patients' age ranging from 5 to 50 years old showed a high frequency of isolation of diarrheic E. coli. Our result is similar to that obtained for patients of ages ranging between 20 to 50 years old (20 to 30 years old, 26.89%; 30 to 40 years old, 18.49%; 40 to 50 years old, 30.25%) by Marbou et al [36]. However, in this study, no isolates were obtained from children aged between 0 to 5 years old.…”
Section: Discussionsupporting
confidence: 91%
“…Diarrheic E. coli was isolated with a significantly higher proportion than other enteric pathogens. If here we reported a first analysis of common enteric pathogens in other to show the real contribution of each pathogen in cases of gastroenteritis in Douala, especially pathogenic Escherichia coli, a recent study highlighted the important involvement of diarrheic E. coli associated with gastroenteritis in the city of Mbouda, West region in Cameroon (19.7% of cases) [36]. If Escherichia coli is a commensal bacterium representing 80% of digestive flora, it is easily found in high proportions using classical media as in some studies, which unfortunately did not provide specific data about the proportion of pathogenic strains.…”
Section: Discussionmentioning
confidence: 87%
“…Similar to our previous studies, DEC‐associated clinical symptoms are much less compared to cholera and Rotavirus gastroenteritis (Dutta et al, 2013; Nair et al, 2010). A recent study in Cameroon suggested that among DEC‐associated diarrhoeal patients, only fever and vomiting were seen in EPEC‐infected cases (Marbou et al, 2020). However, in Kolkata, these symptoms remain prominent in all the DEC cases regardless of their pathotypes.…”
Section: Discussionmentioning
confidence: 99%
“…MDR strains were subjected to PCR for the presence of the following AMR determining genes: bla TEM , bla OXA‐1 , bla CTX‐M3 , bla SHV for β‐lactams (Maynard et al, 2003); qnrB , qnrS and aac6'‐Ib‐cr for plasmid‐mediated quinolone resistance, sul2 and dfrA1 for sulfamethoxazole–trimethoprim (SXT) resistance; strA and aadA for streptomycin (aminoglycoside); catI for chloramphenicol and tetB for tetracycline group of antibiotics using the primer sets listed in Table S1 (Marbou et al, 2020; Sarkar et al, 2015; Sunde & Norström, 2005). The PCR mixture (total volume, 30 μl) consists of a final concentration of 1X Standard Taq Reaction Buffer (NEB, USA), 0.33 mM dNTP mixture, 0.33 μM of each forward and reverse primer (Sigma), 1 U of Taq DNA Polymerase (NEB, USA) and 50–80 ng of template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Resistance determinants to ampicillin (bla TEM and bla Oxa ) were found in 28.57% of the isolates. Additionally, cat1 and cat2 genes were noted in chloramphenicol resistant strains while tetA, tetB encoding resistance to tetracycline, dfr12, dfr7, dfr1a to sulphamethoxazole-trimethoprim, and sul1 gene to sulfonamide were present in more than 85% of the EIEC isolates [169]. In a large-scale study of Shigella and EIEC isolates from eight countries in four continents between 1971 and 1999, 48% of EIEC isolates were resistant to tetracycline [170].…”
Section: Antibiotic Resistance In Eiecmentioning
confidence: 99%